Soybean AROGENATE DEHYDRATASES (GmADTs): involvement in the cytosolic isoflavonoid metabolon or trans-organelle continuity? - Clayton, Emily J.; Islam, Nishat S.; Pannunzio, Kelsey; Kuflu, Kuflom; Sirjani, Ramtin; Kohalmi, Susanne E.; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2024)
Soybean (Glycine max) produces a class of phenylalanine (Phe) derived specialized metabolites, isoflavonoids. Isoflavonoids are unique to legumes and are involved in defense responses in planta, and they are also necessary for nodule formation with nitrogen-fixing bacteria. Since Phe is a precursor of isoflavonoids, it stands to reason that the synthesis of Phe is coordinated with isoflavonoid production. Two putative AROGENATE DEHYDRATASE (ADT) isoforms were previously co-purified with the soybean isoflavonoid metabolon anchor ISOFLAVONE SYNTHASE2 (GmIFS2), however the GmADT family had not been characterized. Here, we present the identification of the nine member GmADT family. We determined that the GmADTs share sequences required for enzymatic activity and allosteric regulation with other characterized plant ADTs. Furthermore, the GmADTs are differentially expressed, and multiple members have dual substrate specificity, also acting as PREPHENATE DEHYDRATASES. All GmADT isoforms were detected in the stromules of chloroplasts, and they all interact with GmIFS2 in the cytosol. In addition, GmADT12A interacts with multiple other isoflavonoid metabolon members. These data substantiate the involvement of GmADT isoforms in the isoflavonoid metabolon.